The IG-DMR and the MEG3-DMR at human chromosome 14q32.2: hierarchical interaction and distinct functional properties as imprinting control centers. - Masayo Kagami; Maureen J O'Sullivan; Andrew J Green; Yoshiyuki Watabe; Osamu Arisaka; Nobuhide Masawa; Kentarou Matsuoka; Maki Fukami; Keiko Matsubara; Fumiko Kato; Anne C Ferguson-Smith; Tsutomu Ogata (PLoS Genetics)
Human chromosome 14q32.2 harbors the germline-derived primary DLK1-MEG3 intergenic differentially methylated region (IG-DMR) and the postfertilization-derived secondary MEG3-DMR, together with multiple imprinted genes. Although previous studies in cases with microdeletions and epimutations affecting both DMRs and paternal/maternal uniparental disomy 14-like phenotypes argue for a critical regulatory function of the two DMRs for the 14q32.2 imprinted region, the precise role of the individual DMR remains to be clarified. We studied an infant with upd(14)pat body and placental phenotypes and a heterozygous microdeletion involving the IG-DMR alone (patient 1) and a neonate with upd(14)pat body, but no placental phenotype and a heterozygous microdeletion involving the MEG3-DMR alone (patient 2). The results generated from the analysis of these two patients imply that the IG-DMR and the MEG3-DMR function as imprinting control centers in the placenta and the body, respectively, with a hierarchical interaction for the methylation pattern in the body governed by the IG-DMR. To our knowledge, this is the first study demonstrating an essential long-range imprinting regulatory function for the secondary DMR.